Islam dan Human Trafficking - Febriana Fauzi, Niki Alma (MUWAZAH, 2017)
This article examines the issue of human trafficking at once how did the Prophet effort in countering it in the early period of Islam. Indeed, the term of human trafficking has not arisen yet in the Prophet’s period. However, because the human trafficking was considered as a modern slavery, then the hadith that narrated regarding slavery practices at the time it can be as data of this study. This study concludes the practice of the elements human trafficking have been in the Prophet’s period, even it far away before that. Precisely Prophet Muhammad with Islam eradicates the practice of slavery bit by bit. At least, there are four efforts that the Prophet did exterminate the slavery at the time: First, to elevate the slave’s level for equaling the normal human being and to act good to the slave. Second, to motivate the Companions in order to compete to liberate the slave. Third, to intimidate those who do the practices of human trafficking. Fourth, to make the liberation of slavery as the mechanism to apply the sanction for the infraction of religion teachings (kaffārah).